Rainwater Harvesting from Urban Coastal Cities Using Recharging Wells: A Case Study of Egypt - Mohamed Gabr; Hamdy El-Ghandour; Samar Elabd (Port Said Engineering Research Journal, 2022)
Rainwater harvesting is becoming increasingly popular among urban planners across the world as a source of alternative water in integrated water resource management plans. In this study, to mitigate urban inundation, avoid rainfall mixing with municipal sewerage, and harvest rainwater, a design methodology for artificial recharge well in urban areas is proposed. A brief summary of some Egyptian governorates that harvested rainwater and the corresponding techniques for rainwater harvesting are presented. Five case studies from Egyptian coastal cities were chosen to examine rainwater harvesting (RWH) using recharging wells systems: Marsa Matrouh, part of Dabaa, Zaheria region in Alexandria, part of Baltim, and 1st Department Region in Al-Arish. Groundwater recharge and surface runoff volumes are evaluated in two scenarios: the number of RWH and no RWH. A comparison between harvested volumes of water corresponding to these two conditions is presented and analyzed. The proposed design and construction of the recharge wells show a recharge well diameter of 0.45 m, discharge of 25.8 m3/h in sandy strata of a depth of 20 m from the ground surface, and a permeability coefficient of 25 m/day. Using the recharge wells system significantly impacted the regional water cycle and reduced saltwater intrusion in coastal aquifers. Recharging rainwater in local aquifers beneath cities via recharging wells is the most cost-effective method for RWH from metropolitan areas.